Effects of customer industry competition on suppliers: Evidence from product market competition shocks - Selvam, Srinivasan (Journal of Banking & Finance, 2020)
We examine the effect of increased customer industry competition on relationships with suppliers, using exogenous variation in industry-level tariffs. We find that customers facing significant tariff reductions increase output by increasing product purchases and maintaining longer relationship durations with existing suppliers. These results are concentrated in strategically important suppliers such as those that have stronger prior relationship ties to customers and among those suppliers that are financially constrained due to capacity constraints among suppliers. However, customers who increase purchases from financially constrained suppliers perform poorly in the post-tariff reduction period. Overall, our results indicate that an increase in customer industry competition improves suppliers’ bargaining power and has both intended and unintended consequences for customers’ trading relationships and future performance.